Geopolymers and Other Geosynthetics - Alshaaer, Mazen; Jeon, Han-Yong (IntechOpen, 2020)
Geopolymers are applied to material classes that are chemically transformed from low crystallinity aluminusilicates to three-dimensional inorganic polymers (tectosilicates). The resulting material has properties similar to natural minerals, so it is called artificial rock. However, these materials exhibit a chemical composition and mineralogical structure similar to feldspar, feldspathoidal, and zeolites consisting of a polymeric Si-O- Al framework, with a microcrystalline or an amorphous structure. Although geopolymers have attractive engineering and environmental characteristics, there are some challenges in commercializing these materials. In this book, these challenges will be addressed along with introducing the functional geopolymers as an effective approach to commercializing these materials and making them economically feasible.